FAKTOR - FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PADA PT. TELKOM DIVISI REGIONAL VII (PERSERO) KOTA MAKASSAR - Naidah, HJ; Hermansyah, Hermansyah (Jurnal Ekonomi Balance, 2017)
Abstract This study aims to determine factors Employee productivity at PT. Telkom Regional Division VII (Persero) Makassar City, viewed from aspects of education level, work experience and gender. This study uses cross section data on 30 labor respondents at PT. Telkom Regional Division VII (Persero) Makassar. Data were analyzed by using multiple regression analysis using SPSS program. The findings of this study indicate that the factors of labor productivity at PT. Telkom Regional Division VII (Persero) Makassar City consisting of education level, work experience and gender simultaneously (together) have a significant effect on employee productivity at PT. Telkom Regional Division VII (Persero) Makassar City Year 2017. This is evidenced by the results based on test results coefficient determination R square obtained 0.477 results. meaning that productivity factors together affect employee performance of 47.7%. the rest is influenced by other factors outside this study. Based on linear regression test result got unstandarizedcoefficient value B from education level 0,522, bigger than work experience equal to 0,322. and a smaller gender of 0.211 This means that 52.2%, employee performance is influenced by the level of education. From the results of this study can be concluded that the factors are more dominant in improving employee productivity.